Designing and Evaluating a Catalog of Micro Frontends Anti-patterns - Silva, Nabson; Conte, Tayana (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2026: Anais do XXXIX Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2026.19415, 2026)
Micro frontend (MFE) is an architectural style that decomposes a monolithic frontend application into smaller, manageable, and independently deployable slices. Despite its increasing adoption, the field remains relatively underexplored, particularly in terms of identifying challenges and documenting best practices. Therefore, the goal of this Master’s Thesis is to propose and evaluate an artifact that supports developers in implementing MFE architectures. We introduce a catalog of MFE anti-patterns that document common problems and practical solutions. After proposing the catalog’s initial version, we conducted three empirical studies, a Personal Opinion Survey, a Controlled Experiment, and Multivocal Literature Review. After each study, we refined the catalog to produce a final version that helps developers identify, solve, and prevent problems when working with MFE architectures. The contributions of this Thesis include centralized documentation of common issues and solutions when developing MFE architectures, empirical evidence on how the catalog can be used, a web application that showcases the anti-patterns and promotes collaboration within industry practitioners, and the development of MFE teaching material that instructors can integrate into software architecture curricula. We believe that the results of this work have the potential to drive significant advances in both the practice and theory of MFE, helping shape future research and improve industry adoption.